(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article analyzes the functional directions of abbreviations used in English and Uzbek from a linguistic, social and communicative point of view. Abbreviations are an important phenomenon of modern linguistics, arising from such needs as speech economy, conciseness, and rapid information exchange. Abbreviations widely used in English are actively entering the Uzbek language as a result of globalization processes, they perform a special communicative function in such areas as technology, politics, economics, medicine, education, and Internet communication. The article studies the structural features of English and Uzbek abbreviations, their phonetic-morphological adaptation, semantic functions, as well as the mechanisms of their use in the official style, mass media, scientific speech and Internet discourse. The study shows the similarities and differences in the two language systems and highlights the impact of abbreviations on language dynamics, terminology development and communication efficiency.